Investigation of exosomes in aged human fibroblasts cultured in serum-free medium - Nadia Ghobeishavi; Amrolah Mosfatazade; Bagher Seyedalipour (Journal of Current Oncology and Medical Sciences)
Introduction: Exosomes are small vesicles (30 to 100 nm) crucial for intercellular communication and influence various biological and pathological processes. This study examined exosome secretion in human skin fibroblasts in vitro.